Perceptions et Opinions d’Enseignants du Cycle Secondaire relatives à l’Enseignement de la Classification du monde Végétal - Lhoussaine, Maskour; Anouar, Alami; Boujemaa, Agorram; Moncef, Zaki (European Scientific Journal, ESJ, 2019)
This paper focuses on identifying the perceptions and opinions of high school teachers about plant classification and its teaching. It also aims at shedding light on the difficulties and obstacles that hinder plant taxonomy teaching at this school level. To this end, a questionnaire-based survey was conducted among 216 junior high school and senior high school teachers.The analysis of the responses of the teachers has enabled to identify numerous erroneous and diversified conceptions about the scientificity and the importance of the plant taxonomy and its teaching, which could constitute obstacles for student plant taxonomy learning.The analysis of the teachers’ responses led to the conclusion that the university and professional training followed by these teachers does not seem to have corrected these misperceptions. The results also show that teachers and their students are too unmotivated to learn classification. Given this situation, it is essential to develop active methods for teaching classification, promoting practical activities that can increase student motivation and address the classification from a scientific perspective, which helps to explain and to show the diversity of parenthood of all living beings taking into account their history. L’étude, objet du présent article, vise à identifier les perceptions et les opinions d’enseignants du cycle secondaire sur la classification des plantes et son enseignement. Elle vise aussi à caractériser les difficultés et obstacles qui entravent l’enseignement de la taxonomie végétale dans ce cycle. Pour ce faire, une enquête par questionnaire menée auprès de 216 enseignants du secondaire collégial et qualifiant. L’analyse des réponses des enseignants a permis d’identifier nombreuses conceptions erronées et diversifiées sur la scientificité, sur l’importance de la taxonomie végétale et son enseignement qui pourraient constituer des obstacles entravant l’apprentissage de la taxonomie végétale par les élèves. Les résultats de cette recherche permettent de conclure que la formation universitaire et professionnelle suivie par ces enseignants semble ne pas avoir permis de corriger ces conceptions erronées. Les résultats montrent aussi que les enseignants et leurs élèves sont démotivés pour apprendre la classification, d’où il est primordial de développer des méthodes actives pour l’enseignement de la classification en privilégiant des activités pratiques qui permettent d’augmenter la motivation des apprenants, ainsi que de traiter le thème de la classification dans une perspective scientifique qui permet d’expliquer et de montrer la diversité et la parenté de tous les êtres vivants en prenant en considération leurs histoire.